2020
DOI: 10.1186/s13578-020-00424-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging functions and clinical applications of exosomes in human oral diseases

Abstract: Exosomes are cell-derived membranous vesicles of endosomal origin secreted by all type of cells and present in various body fluids. Exosomes are enriched in peptides, lipids, and nucleic acids, emerging as vital modulators in intercellular communication. Exosomes are increasingly being evaluated as biomarkers for diagnosis and prognosis of diseases, because the constituents of exosomes could be reprogrammed depending on the states of diseases. These features also make exosomes a research hotspot in oral diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 126 publications
0
23
0
Order By: Relevance
“…An advantage of using exosome-derived miRNAs as biomarkers is that they are protected from degradation by RNases and thus are quite stable [ 26 , 27 ]. Furthermore, the vesicles display on their surface the antigenic markers of the cells from which they were derived, allowing enrichment of vesicles from a particular tissue source [ 84 , 85 ]. For therapeutic applications, exosomes could be used to deliver not only miRNAs but also proteins and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of using exosome-derived miRNAs as biomarkers is that they are protected from degradation by RNases and thus are quite stable [ 26 , 27 ]. Furthermore, the vesicles display on their surface the antigenic markers of the cells from which they were derived, allowing enrichment of vesicles from a particular tissue source [ 84 , 85 ]. For therapeutic applications, exosomes could be used to deliver not only miRNAs but also proteins and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…DPSC-exos also have the potential to induce endothelial cell proliferation and pro-angiogenic factor expression, playing an important role in dentin formation and angiogenesis [137]. It has been reported that cell type-specific exosomes can induce lineage-specific differentiation of stem cells [138]; thus, the attachment of dental stem cell-derived exosomes, including DPSC-exos, SHED-exos, and HERS-exos, to biomaterials such as collagen gel may be a more efficient and secure alternative option for pulp regeneration [139,140], while the exact molecular mechanisms remain to be investigated [141].…”
Section: Exosome-mediated Pulp Regenerationmentioning
confidence: 99%
“…While various studies have shown that OLP is a widely recognized chronic inflammatory autoimmune responsedriven disorder, the precise pathogenesis remains unknown 1,5,6,[15][16][17][18] . Some researchers found that emotional stress, infection and hypersensitivity contribute to OLP onset 1,6,19 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…OLP is considered a T cell-mediated autoimmune disorder in which apoptosis of basal epithelial cells is caused by clusters of differentiation 8 (CD8)+ T cells. Its function is uncertain, but in the exacerbation and continuation of the oral lichen planus, a cytokine complex network(such as TNF-α, IFN-γ, TGF-β, IL-1, 2, 4, 5, 6, 8, 10, 12, 17, 18, and IL-22) plays an significant role 5,14,18,[20][21][22] . Other researchers suggest that the cellmediated immune system starts with the expression of keratinocytes antigen; this step is accompanied by the movement of T cell lymphocytes directly activated by an antigen binding to the main histocompatibility complex (MHC)-1 on keratinocytes or activated CD4 + lymphocytes 13 .In exchange, the activated CD8 + T cells kill the basal keratinocytes by tumor necrosis factor (TNF)-alpha, Fas-FasLmediated or granzyme B-activated apoptosis 13 .…”
Section: Pathophysiologymentioning
confidence: 99%